Environmental factors determine the occurrence of pulmonary tuberculosis - Eppy Setiyowati; Khamida Khamida; Nurul Kamariyah; Budhi Setianto; Netty Mawardah Hatmanti; Difran Nobel Bistara; Erika Martining Wardani (Alma Ata University Press, 2023)
Background: Environment consisting of residential density, house ventilation, room humidity, and lighting, is regarded as one of the factors causing the transmission of pulmonary tuberculosis (TB). The current research aimed to figure out the environmental factors determining the occurrence of pulmonary TB in Surabaya City. Objectives: the purpose of the current study was to figure out the environmental factor determining the incidents of pulmonary tuberculosis (TB) in Surabaya CityMethods : This was observational research carried out by a cross-sectional approach. People with pulmonary TB registered for treatment at the Perak Timur Community Health Center and Jagir Community Health Center in Surabaya City were recruited as the research population. Meanwhile, the research samples were patients with pulmonary TB in both Community Health Centers. Simple random sampling was utilized to collect 130 patients as respondents. The data obtained were then analyzed using univariate and bivariate logistic regression.Results: The bivariate statistical test on the four research variables showed that residential density had OR=0.671, house ventilation had OR=2.874, room humidity had OR=1.231, and house lighting had OR=1.170. Fourth, environmental factors are not the cause of TB disease, because the results of statistical tests show that the OR value is above 0.5Conclusions: It can be concluded that residential density, lighting, and house ventilation did not influence the occurrence of pulmonary tuberculosis. It was more likely that it was caused by factors which do not come from the living environment. Suggestions for future research need to be an air swab examination around the residence of TB patients